Adrenal ganglioneuromas: a retrospective multicentric study of 104 cases from the COMETE network. Issue 4 (27th August 2021) - Deflorenne, Elisa; Peuchmaur, Michel; Vezzosi, Delphine; Ajzenberg, Christiane; Brunaud, Laurent; Chevalier, Nicolas; Christin-Maitre, Sophie; Decoudier, Bénédicte; Driessens, Natacha; Drui, Delphine D; Gilly, Olivier; Goudet, Pierre; et al.
Abstract: Objective: Adrenal ganglioneuromas are rare, differentiated, neuroblastic tumors that originate from the peripheral sympathetic nervous system. Because of their rarity, information is limited, derived from small cases series. Our objective was to characterize this tumor and provide help for its management. Methods: A retrospective multicenter analysis of adrenal ganglioneuromas from 20 French centers belonging to the COMETE network and one Belgian center. Results: Among the 104 cases identified, 59.6% were women ( n  = 62/104), median age at diagnosis was 29 years, with 24 pediatric cases. 60.6% ( n  = 63/104) were incidentalomas. Ganglioneuromas were non-secreting tumors in 90.8% of cases ( n  = 89/98), whereas the preoperative hormonal evaluation was indeterminate for 9.2% of patients ( n  = 9/98). CT imaging, performed on 96 patients, revealed large tumors (median diameter of 50 mm) with a non-contrast density > 10 Hounsfield units in 98.1% ( n  = 52/53) and calcifications in 64.6% of cases ( n  = 31/48). Increased uptake on 123 I-MIBG scintigraphy and 18 F-FDG-PET/CT was observed in 26.7% ( n  = 8/30) and 42.2% ( n  = 19/45) of the tumors, respectively. All 104 patients underwent surgery. No recurrence was observed among the 42 patients who had an imaging follow-up (mean 29.6 months, median 18 months (4–156)). Conclusion: Adrenal ganglioneuromas are large tumors, mostly nonfunctioning, without benign imaging features. Although the duration of follow-up was limited in our series, no recurrence was identified. A review of the literature confirms the absence of postoperative recurrence. Based on all available data, in the absence of special circumstances (genetic form, uncertain histological diagnosis), long-term follow-up is not necessary after complete surgery for patients with an adrenal ganglioneuroma.